Data on spatial variation in soil nutrient supply and liming (Ethiopia validation data) - Sida, Tesfaye Shiferaw (Harvard, 2025)
This dataset contains plot-level soil attributes emphasizing acidity and fertility covariates. Chemical variables include soil pH (H₂O/KCl), exchangeable acidity (ex_ac, cmolc kg⁻¹), exchangeable Al and Al saturation (ac_sat, %), effective/total CEC (CEC/ECEC, cmolc kg⁻¹), base saturation (%), and exchangeable bases (Ca, Mg, K, Na; cmolc kg⁻¹). Organic matter and macronutrients are represented by organic carbon (OC, %), total nitrogen (TN, %), and plant-available phosphorus (av_p_est, mg kg⁻¹; method-specific), with optional sulfur and selected micronutrients (e.g., Zn) where available. Physical variables include texture fractions (clay, silt, sand, %), with soil organic matter (SOM) reported where measured or derived. Each record is standardized for unit consistency, and derived indices (e.g., ac_sat, ECEC, base saturation) are computed from primary measurements to provide coherent acidity and nutrient status indicators.